Synthesis and electroluminescent properties of highly efficient anthracene derivatives with bulky side groups - Kim, Soo-Kang; Yang, Bing; Park, Young-Il; Ma, Yuguang; Lee, Jun-Yeob; Kim, Hyoung-Juhn; Park, Jongwook (ELSEVIER, 2009)
Three new asymmetric light emitting organic compounds were synthesized with diphenylamine or triphenylamine side groups; 10-(3,5-diphenylphenyl)-N.N-diphenylanthracen-9-amine (MADa), 4-(10-(3,5- diphenylphenyl)anthracen-9-yl)-N,N-diphenylaniline (MATa), and 4-(10-(3',5'-diphenylbiphenyl-4-yl)anthracen-9-yl)-N,N-diphenylaniline (TATa). MATa and TATa had a PLmax at 463 nm. in the blue region, and MADa had a PLmax at 498 nm. MADa and MATa had T. values greater than 120 degrees C, and TATa had a T-g of 139 degrees C. EL devices containing the synthesized compounds were fabricated in the configuration: ITO/4,4', 4 ''-tris(N-(2-naphthyl)-N-phenyl-amino)-triphenylamine (2-TNATA) (60 nm)/N.N'-bis(naphthalen- 1-yl)-N,N'-bis(phenyl)benzidine (NPB) (15 nm)/MADa or MATa or TATa or 9,10-di(2'-naphthyl)anthracene (MADN) (30 nm)/8-hydroxyquinoline aluminum (Alq(3)) (30 nm)/LiF (1 nm)/Al (200 nm). The efficiency and color coordinate values (respectively) were 10.3cd/A and (0.199, 0.152; bluish-green) for the MADa device, 4.67cd/A and (0.151, 0.177) for the MATa device, and 6.07 cd/A and (0.149, 0.177) for the TATa device. The TATa device had a high external quantum efficiency (EQE) of 6.19%, and its luminance and power efficiencies and life-time were more than twice those of the MADN device. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: LIGHT-EMITTING DEVICES; BLUE ELECTROLUMINESCENCE; EMITTERS; TRANSPORT; DIODES